Designing integrated conceptual model of talent management using meta-synthesis approach / Mohammad Koohi Khor ... [et al.] - Khor, Mohammad Koohi; Kamalian, Amin Raza; Yaghoubi, Nour Mohammad; Pourezzat, Aliasghar (Research Management Centre (RMC), 2020)
It is widely accepted that in the recent economic downturn, there are many demands for talent, and thus many organisations employ talent management systems to create a competitive advantage. The lack of an integrated talent management process, as a strategic approach, leads to a waste of time, effort, and money. The present study aims to provide an integrated model of talent management using the meta-synthesis approach. This study falls within the category of applied research in terms of purpose and meta-synthesis in terms of methodology. The researchers in this study, in a meta-synthesis way, have carefully scrutinised the topic and combined the findings of both quantitative and qualitative research studies. In this regard, 3615 research studies in the field of talent management and integrated talent management were selected by searching in Web of Science (2008-2018), Magiran, University of Tehran's magazines, and international databases of papers and books; and finally, based on 106 studies underwent content analysis, dimensions and codes were extracted, and the significance and priority of each one were determined using the Shannon entropy. Based on research findings, management and planning codes for succession, learning, and talented employee involvement; organisational acceptance; and talent strategy relationship with business strategy, progression management, and organisational culture had the highest impact. Finally, according to the extracted components, the proposed model was presented.